2022
DOI: 10.1093/jxb/erac013
|View full text |Cite
|
Sign up to set email alerts
|

Polycomb proteins control floral determinacy by H3K27me3-mediated repression of pluripotency genes in Arabidopsis thaliana

Abstract: Polycomb group (PcG) protein-mediated histone methylation (H3K27me3) controls the correct spatiotemporal expression of numerous developmental regulators in Arabidopsis. Epigenetic silencing of the stem cell factor WUS in floral meristems (FMs) depends on H3K27me3 deposition by PcG proteins. However, the role of H3K27me3 in silencing of other meristematic regulator and pluripotency genes during FM determinacy has not yet been studied. To this end, we report the genome-wide dynamics of H3K27me3 levels during FM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 98 publications
0
9
0
Order By: Relevance
“…In flower stage 6, KNU represses CLV3 and WUS (Shang et al, 2021). Many of these transcriptional regulations are supported or driven by changes in H3K4me3 (K4m) or H3K27me3 (K27m), which is also confirmed by the flower indeterminacy phenotypes by loss of H3K27me3 demethylases REF6, ELF6 and JMJ13 or PRC2 (Yan et al, 2018;Müller-Xing et al, 2022). Other genes directly or indirectly involved in WUS silencing: ARGONAUTE1 (AGO1), AUXIN RESPONSE TRANSCRIPTION FACTOR3 (ARF3/ETT), CRABS CLAW (CRC), FAR-RED ELONGATED HYPOCOTYLS3 (FHY3), PERIANTHIA (PAN), REBELOTE (RBL), SQUINT (SQN), YUCCA4 (YUC4) and the HD-ZIP class III transcription factors CORONA (CNA), PHABULOSA (PHB), PHAVOLUTA (PHV) and REVOLUTA (REV).…”
Section: Direct and Indirect Regulation Of Pluripotency Factors By Ep...mentioning
confidence: 79%
See 3 more Smart Citations
“…In flower stage 6, KNU represses CLV3 and WUS (Shang et al, 2021). Many of these transcriptional regulations are supported or driven by changes in H3K4me3 (K4m) or H3K27me3 (K27m), which is also confirmed by the flower indeterminacy phenotypes by loss of H3K27me3 demethylases REF6, ELF6 and JMJ13 or PRC2 (Yan et al, 2018;Müller-Xing et al, 2022). Other genes directly or indirectly involved in WUS silencing: ARGONAUTE1 (AGO1), AUXIN RESPONSE TRANSCRIPTION FACTOR3 (ARF3/ETT), CRABS CLAW (CRC), FAR-RED ELONGATED HYPOCOTYLS3 (FHY3), PERIANTHIA (PAN), REBELOTE (RBL), SQUINT (SQN), YUCCA4 (YUC4) and the HD-ZIP class III transcription factors CORONA (CNA), PHABULOSA (PHB), PHAVOLUTA (PHV) and REVOLUTA (REV).…”
Section: Direct and Indirect Regulation Of Pluripotency Factors By Ep...mentioning
confidence: 79%
“…We recently revealed that during FM arrest also several other pluripotency genes, including STM and other TALE KNOX genes, are silenced by H3K27me3 (Figure 1F). This Frontiers in Plant Science frontiersin.org synchronized silencing of several pluripotency genes could accelerate FM determinacy in a way that cannot be achieved by silencing WUS alone (Müller-Xing et al, 2022).…”
Section: Stem-cell Determinacy During Flower Development By Epigeneti...mentioning
confidence: 99%
See 2 more Smart Citations
“…Many machine learning algorithms, such as support vector machine (SVM) [10] , [11] , [12] , deep learning (DL) [13] , [14] , [15] , [16] , [17] , [18] , [19] , extreme boosting algorithm (XGBoost) [20] , [21] , [22] , [23] , [24] , and stacking ensemble models [25] , [26] , [27] , [28] , [29] , [30] , etc., have been developed for protein function, structure, subcellular localization, and even other biological processes. Different feature descriptors such as amino acid composition (AAC) [31] , [32] , [33] , reduced amino acid composition [34] , [35] , [36] , g -gap dipeptide composition [37] , [38] , and secondary structure features [39] , etc., were adopted to represent protein sequences. While there is still no computational method to identify IBPs in phages, this study aims to design a novel model for IBP prediction.…”
Section: Introductionmentioning
confidence: 99%